Development and evaluation of a neonatal nurse practitioner mentoring workshop - Moss, Colleen Reilly (Journal of the American Association of Nurse Practitioners, 2024)
New graduate neonatal nurse practitioners (NNPs) need more than an orientation; they need mentoring to facilitate successful role transition and enhance job satisfaction. A gap exists in the literature about mentoring participant training and launching of successful programs for NNPs. This article provides an overview of the development and evaluation of a nurse practitioner (NP) mentoring workshop before the start of a formalized mentoring program. Workshop participants attended a half-day education event with an emphasis on mentoring program expectations, mentor and mentee roles, and effective communication. After the workshop, participants completed an electronic survey to evaluate satisfaction with the teaching and areas for improvement. From January 2022 through January 2023, newly hired NPs paired with experienced NP mentors participated in this structured workshop. Twenty-eight participants in two cohorts evaluated the workshop to identify meaningful aspects of the presentations and areas for improvement. Participants reported high levels of satisfaction with the interactive components of the 4-hr workshop. An interactive mentoring workshop helps participants establish realistic expectations and mutual goals. Further study is needed to identify time- and cost-efficient strategies in the preparation of effective mentoring participants to enhance the quality of mentoring programs.